2013
DOI: 10.1088/0004-637x/768/1/1
|View full text |Cite
|
Sign up to set email alerts
|

THE CLUSTER AND FIELD GALAXY ACTIVE GALACTIC NUCLEUS FRACTION ATz= 1-1.5: EVIDENCE FOR A REVERSAL OF THE LOCAL ANTICORRELATION BETWEEN ENVIRONMENT AND AGN FRACTION

Abstract: The fraction of cluster galaxies that host luminous AGN is an important probe of AGN fueling processes, the cold ISM at the centers of galaxies, and how tightly black holes and galaxies co-evolve. We present a new measurement of the AGN fraction in a sample of 13 clusters of galaxies (M ≥ 10 14 M ) at 1 < z < 1.5 selected from the Spitzer/IRAC Shallow Cluster Survey, as well as the field fraction in the immediate vicinity of these clusters, and combine these data with measurements from the literature to quanti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
176
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(203 citation statements)
references
References 118 publications
(164 reference statements)
22
176
5
Order By: Relevance
“…The resulting mean contamination of AGN per cluster is (1 + z) 3.3 × 6.6 × 10 42 erg s −1 in the rest-frame 0.5-2 keV band, which has to be rescaled up self-consistently using cluster K-correction factors of ∼ 1.5. This model is in a very good agreement with the results of Martini et al (2013), who measured AGN activity in 1 < z < 1.5 clusters at an average level of 10 44 erg s −1 in the 0.5-8 keV band. In our highest redshift bin, the model predicts an AGN contribution of 4.7 × 10 43 erg s −1 , which, on average, is still a subdominant contribution to the observed flux.…”
Section: A P P E N D I X C : M O D E L I N G T H E S E L E C T I O N supporting
confidence: 91%
“…The resulting mean contamination of AGN per cluster is (1 + z) 3.3 × 6.6 × 10 42 erg s −1 in the rest-frame 0.5-2 keV band, which has to be rescaled up self-consistently using cluster K-correction factors of ∼ 1.5. This model is in a very good agreement with the results of Martini et al (2013), who measured AGN activity in 1 < z < 1.5 clusters at an average level of 10 44 erg s −1 in the 0.5-8 keV band. In our highest redshift bin, the model predicts an AGN contribution of 4.7 × 10 43 erg s −1 , which, on average, is still a subdominant contribution to the observed flux.…”
Section: A P P E N D I X C : M O D E L I N G T H E S E L E C T I O N supporting
confidence: 91%
“…Accounting for AGN detected using multiple diagnostics, AGN are found in 181 unique galaxies in the full SPIRE sample. This corresponds an AGN rate of 10.3 ± 0.8% in the full SPIRE sample, a value broadly similar to preliminary studies investigating the prevalence of AGN in sub-mm-selected samples at similar redshifts (e.g., Pope et al 2008;Serjeant et al 2010) and one which only slightly exceeds the detection rates of AGN in surveys of optically-selected galaxies at a variety of different redshifts (e.g., Kauffmann et al 2003;Martini et al 2009Martini et al , 2013Montero-Dorta et al 2009;Sarajedini et al 2011;Klesman et al 2012). While this comparison suggests that the presence of a starburst in a galaxy does not increase the chances that its nucleus will be undergoing a powerful active phase, these comparisons are subject to a slew of observational and selection biases.…”
Section: The Prevalence Of Agn In Starbursting Galaxiessupporting
confidence: 87%
“…More importantly, after having complete spectroscopy for their X-ray point source sample, Haines et al (2012) argue that X-ray AGN found in massive clusters are an infalling population, which is "extinguished" later, and confirm the suppression in rich clusters. On the other hand, Martini et al (2013) argue that this trend is not confirmed for a sample of high-redshift clusters (1.0 < z < 1.5), where the presence of luminous X-ray AGN (L (0.5−2 keV) > 10 43 erg/s) is consistent with the field. We note, however, that the high-redshift regime studied and the large AGN photometric redshift uncertainties (σ z = 0.12(1 + z), double that of normal galaxies) introduce some level of uncertainty to the results.…”
Section: Introductionmentioning
confidence: 83%